Cost-effectiveness of dabigatran for stroke prevention in atrial fibrillation in Switzerland (Swiss Medical Weekly, 2012)
OBJECTIVES: Atrial fibrillation is a major risk factor for ischemic stroke and anticoagulation therapy is indicated to reduce risk. Dabigatran is a new oral anticoagulant that does not require INR monitoring. This study evaluated the cost-effectiveness of dabigatran versus vitamin K antagonists for stroke prevention in atrial fibrillation in Switzerland. METHODS: A Markov model simulating the course of treatment and occurrence of clinical events in two treatment arms over the lifetime of patients was adapted to the Swiss context. The adaptation included the cost of anticoagulation therapy and clinical events in Switzerland. The cost of inpatient care was estimated on data of all inpatient hospital stays in 2008. The calculation of outpatient care costs was based on peer reviewed studies, expert interviews and local tariffs. RESULTS: Patients treated with dabigatran had a higher life expectancy and experienced more quality adjusted life years (QALY) while incurring higher costs than patients treated with vitamin K antagonists. The estimated incremental cost-effectiveness ratio (ICER) was CHF 25,108.‒ per QALY with 110 mg and CHF 9,702 per QALY with 150 mg of dabigatran. A sequential dosage scheme, in which 150 mg are administered up to the age of 80 years and 110 mg thereafter, resulted in an ICER of CHF 10,215 per QALY. A sensitivity analysis confirmed that these results are robust. CONCLUSIONS: Dabigatran can be considered cost-effective in comparison with vitamin K antagonists in the Swiss context. The higher drug cost of dabigatran is compensated by savings in INR monitoring, lower cost of clinical events and QALY-gains. Key words:dabigatran; warfarin; marcoumar; oral anticoagulation; atrial fibrillation; stroke prevention; vitamin K antagonist; VKA; cost; cost-effectiveness; QALY; ICER; Switzerland